Toll-like receptor-mediated innate immunity orchestrates adaptive immune responses in HBV infection - Du, Yanqin; Wu, Jun; Liu, Jia; Zheng, Xin; Yang, Dongliang; Lu, Mengji (Frontiers in Immunology, 2022)
Chronic hepatitis B virus (HBV) infection remains to be a substantial global burden, especially for end-stage liver diseases. It is well accepted that HBV-specific T and B cells are essential for controlling HBV infection. Toll-like receptors (TLRs) represent one of the major first-line antiviral defenses through intracellular signaling pathways that induce antiviral inflammatory cytokines and interferons, thereby shaping adaptive immunity. However, HBV has evolved strategies to counter TLR responses by suppressing the expression of TLRs and blocking the downstream signaling pathways, thus limiting HBV-specific adaptive immunity and facilitating viral persistence. Recent studies have stated that stimulation of the TLR signaling pathway by different TLR agonists strengthens host innate immune responses and results in suppression of HBV replication. In this review, we will discuss how TLR-mediated responses shape HBV-specific adaptive immunity as demonstrated in different experimental models. This information may provide important insight for HBV functional cure based on TLR agonists as immunomodulators.